Antecedents on Customer Satisfaction Tuku Coffee Shop: A Perspective Expectation-Confirmation Theory and Kano's Model - Juliana Juliana; Birgitta Stella; Christabella Viana Austine; Elvina Dewi Budiono; Klara Klarissa (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
The purpose of this study was to test the antecedents of overall customer satisfaction using the expectation confirmation theory and Kano's model. Data analysis methods used PLS-SEM. The sampling technique used purposive sampling. The sample analyzed in this study amounted to 200 respondents. The results show that packaging has a significant effect on customer satisfaction, service quality has an impact on customer satisfaction, meaning that the hypothesis is supported so that coffee shop management should pay more attention to packaging and service to consumers which can offer a more memorable experience for customers to create customer satisfaction. But sales promotion does not Significant effect on customer satisfaction means that the hypothesis is rejected. This study is limited in the sample size, research domain and participant coverage. This study suggests a practical canoe model approach and expectation confirmation theory for related organizations and practitioners to correctly identify customer needs and channel resources in the right direction. Fulfilling customer requirements by providing customer satisfaction and pleasure is essential as a golden rule to maintain business continuity in this competitive world. Keywords: packaging, sales promotion, service quality, customer satisfaction